One-Step Synthesis of High-Quality Water-Soluble CdSe Quantum Dots Capped by N-Acetyl-L-cysteine via Hydrothermal Method and Their Characterization - Chunjin Wei; Jinyu Li; Fang Gao; Shuxia Guo; Yongcui Zhou; Dan Zhao (Journal of Spectroscopy)
Novel water-soluble CdSe quantum dots (QDs) have been prepared with N-acetyl-L-cysteine as new stabilizer through a one-step hydrothermal route. The influence of experimental conditions, including reaction time, molar ratio of reactants, and pH value, on the luminescent properties of the obtained CdSe QDs has been systematically investigated. The characterization of as-prepared QDs was carried out through different methods. In particular, we realized qualitative and semiquantitative studies on CdSe QDs through X-ray photoelectron spectroscopy and electron diffraction spectroscopy. The results show that the as-prepared CdSe QDs exhibit a high quantum yield (up to 26.7%), high stability, and monodispersity and might be widely used in biochemical detection and biochemical research.